Deployment of Enterprise Architecture in the Namibian Government: The Use of Activity Theory to Examine the Influencing Factors. Issue 1 (5th December 2017) - Shaanika, Irja; Iyamu, Tiko
Abstract: Government in both developed and developing countries strive to deliver effective and efficient services to its citizens. Hence the rapid increasing use of information technology to enhance service delivery. However, IT carries its own challenges, such as incompatibilities, lack of integration and lack of scalability. Many approaches, from both academic and professional domains have been employed to assess the challenges, for improvement purposes. Government of some countries have therefore introduced enterprise architecture (EA) to addressing IT challenges. Similarly, EA is influenced by many factors, making it not as easy as we are made to understand. Thus activity theory was applied to examine and understand how the challenges manifest into complexities, and in turn, have negative impacts on services delivery. The use of the activity theory (AT) helps to reveal that non‐technical factors were completely ignored or sometimes considered to be less significant to the technical factors. Based on the interpretation of the findings, process, communication, lack of awareness, roles and responsibilities, actors' relationships, policies and people were uncovered as some of the influencing factors in the deployment of EA, in the Namibian government‐wide Ministries. The communication between various business units and IT unit was influenced by those in authority as they make use of their power for individual interest. These types of legitimate actions through roles and responsibilities, contributed to the misalignments of business processes and activities in the deployment of EA in the Namibian government‐wide Ministries. If both technical and nontechnical factors are not considered in the implementation of systems and technologies governments' service delivery will continue to be hampered as depicted in the framework presented in this article.